Associations of Ischemic Lesion Volume With Functional Outcome in Patients With Acute Ischemic Stroke: 24-Hour Versus 1-Week Imaging. Issue 5 (May 2017) - Bucker, Amber; Boers, Anna M.; Bot, Joseph C.J.; Berkhemer, Olvert A.; Lingsma, Hester F.; Yoo, Albert J.; van Zwam, Wim H.; van Oostenbrugge, Robert J.; van der Lugt, Aad; Dippel, Diederik W.J.; Roos, Yvo B.W.E.M.; Majoie, Charles B.L.M.; et al.
Abstract : Background and Purpose—: Ischemic lesion volume (ILV) on noncontrast computed tomography at 1 week can be used as a secondary outcome measure in patients with acute ischemic stroke. Twenty-four–hour ILV on noncontrast computed tomography has greater availability and potentially allows earlier estimation of functional outcome. We aimed to assess lesion growth 24 hours after stroke onset and compare the associations of 24-hour and 1-week ILV with functional outcome. Methods—: We included 228 patients from MR CLEAN trial (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands), who received noncontrast computed tomography at 24-hour and 1-week follow-up on which ILV was measured. Relative and absolute lesion growth was determined. Logistic regression models were constructed either including the 24-hour or including the 1-week ILV. Ordinal and dichotomous (0–2 and 3–6) modified Rankin scale scores were, respectively, used as primary and secondary outcome measures. Results—: Median ILV was 42 mL (interquartile range, 21–95 mL) and 64 mL (interquartile range: 30–120 mL) at 24 hours and 1 week, respectively. Relative lesion growth exceeding 30% occurred in 121 patients (53%) and absolute lesion growth exceeding 20 mL occurred in 83 patients (36%). Both the 24-hour and 1-week ILVs were similarly significantly associated with functional outcome (both P <0.001). In the logistic analyses, the areas under the curve of the receiver–operator characteristic curves were similar: 0.85 (95% confidence interval, 0.80–0.90) and 0.87 (95% confidence interval, 0.82–0.91) for including the 24-hour and 1-week ILV, respectively. Conclusions—: Growth of ILV is common 24-hour poststroke onset. Nevertheless, the 24-hour ILV proved to be a valuable secondary outcome measure as it is equally strongly associated with functional outcome as the 1-week ILV. Clinical Trial Registration—: URL:http://www.isrctn.com . Unique identifier: ISRCTN10888758. Abstract : Supplemental Digital Content is available in the text.